Oral Cavity Disease Incidents in the Framework of World Oral Health Day - Sa'adah, Nikmatus; Sari, Multia Ranum; Putri, Annisa (Journal of Community Engagement and Empowerment, 2025)
Oral and dental health is important to support quality of life, including the ability to speak, eat, and socialize without pain or embarrassment. Dental and oral problems can cause pain, discomfort, infection, sleep disturbances, and high medical costs, which have an impact on decreasing the quality of learning and work productivity. This community service program aims to increase awareness of maintaining oral hygiene, educate how to detect oral diseases early, and encourage regular visits to the dentist every six months. The method is carried out through teledentistry, which utilizes the Surbo Chat application and WhatsApp TanyaPepsodent. The results of this program revealed that 90% of patients did not understand early detection of oral diseases, and 95% of patients had dental problems, with the most cases being caries. The conclusion of this activity is that teledentistry is effective in providing consultation and education related to dental and oral health.